Antitumor Effects and Related Mechanisms of Ethyl Acetate Extracts of Polygonum perfoliatum L. - Li, Qinglin; Fu, Xiaoxuan; Ge, Xinyang; Tao, Feng; Huang, Ping; Ge, Minghua; Jin, Hongchuan (Frontiers in Oncology, 2019)
Polygonum perfoliatum L. belongs to the genus Polygonaceae and has a long history to be used as a Chinese medicinal herb to reduce swelling, control body temperature, and promote detoxification. However, its anticancer activity and mechanisms of action have not been evaluated yet. In the present study, we used several cell lines and xenograft models from different cancers to demonstrate the broad-spectrum anticancer activity of P. perfoliatum L as well as its underlying mechanisms of action in vitro and in vivo. The ethyl acetate extract of P. perfoliatum L showed good anticancer activity and was further fractioned to obtain five active components, including PEA to PEE. Among these fractions, PEC showed the strongest cytotoxicities against various cancer cell lines. It was further observed that PEC inhibited cancer cell growth, arrested cells at G2 phase, and induced apoptosis in vitro and suppressed tumor growth and angiogenesis in vivo in a dose- and time-dependent manner. Furthermore, PEC decreased the expression of vascular endothelial growth factor (VEGF) and micro-vascular density (MVD) in tumor tissues in vivo. It also promoted the proliferation of T and B lymphocytes, increased the activities of natural killer (NK) cells and cytotoxic T lymphocytes (CTLs), enhanced the secretion of interleukin 2 (IL-2) by spleen cells, and raised the levels of IgG, IgG2a, and IgG2b antibodies in tumor-bearing mice in vivo, which were at least partially responsible for the anticancer activity of PEC. In summary, PEC has shown broad-spectrum anticancer activities without causing any host toxicity in vitro and in vivo and may be developed as a preventive and therapeutic agent against human cancer. Further studies are urgently needed to determine the anticancer compounds in PEC and their detailed molecular mechanisms.